Relationships between hemoglobin levels at admission and adverse maternal and perinatal outcomes in patients with preeclampsia - Yanan Lian; Yanxiang Lv; Yuan Qiao; Tongqiang He (PLoS ONE, 2025)
Background Maternal hemoglobin is very important for maternal and perinatal outcomes. Due to the pathophysiological changes in patients with preeclampsia, the influence of hemoglobin on pregnancy outcomes may differ from that in normal pregnant women. Therefore, this retrospective study aimed to evaluate the relationships between maternal hemoglobin levels and adverse maternal and perinatal outcomes in patients with preeclampsia. Methods All clinical data were retrospectively collected from the medical records of a tertiary obstetrics and gynecology hospital in China. This study evaluated the incidence of adverse maternal and perinatal outcomes in patients with preeclampsia with different hemoglobin levels at admission. The odds ratios and 95% confidence intervals for adverse pregnancy outcomes in patients with preeclampsia with anemia and high hemoglobin levels were estimated, with the normal hemoglobin level serving as the control. Results A total of 1,715 patients with preeclampsia with singleton pregnancies were included in this retrospective study. Compared with patients with preeclampsia with normal hemoglobin levels, patients with anemia at admission had a greater risk for postpartum hemorrhage (OR: 3.800; 95% CI: 1.677–8.610) and cardiac dysfunction (OR: 2.860; 95% CI: 0.979–8.356). Moreover, patients with high hemoglobin levels at admission had increased risks of HELLP syndrome (OR: 2.503; 95% CI: 1.198–5.229), SGA (OR: 1.343; 95% CI: 0.997–1.808), neonatal asphyxia (OR: 2.046; 95% CI: 1.107–3.784) and NICU admission (OR: 1.359; 95% CI: 1.060–1.742). However, not all abnormal hemoglobin levels were associated with an increased risk of adverse pregnancy outcomes. Patients with preeclampsia with anemia had a lower risk of adverse perinatal outcomes, including SGA (OR: 0.731; 95% CI: 0.517–1.032) and NICU admission (OR: 0.737; 95% CI: 0.567–0.960). Conclusion This study revealed that both anemia and high hemoglobin levels at admission were related to adverse maternal and perinatal outcomes in patients with preeclampsia. The effects of hemoglobin on adverse maternal and perinatal outcomes in patients with preeclampsia may differ from those in normal pregnant women.